2020
DOI: 10.3892/etm.2020.8761
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of 14‑3‑3η are associated with increased disease risk, activity and duration of rheumatoid arthritis in Chinese patients

Abstract: The aim of the present study was to determine the association between serum 14-3-3η expression levels and disease risk, inflammation level and disease duration in Chinese patients with rheumatoid arthritis (RA). A total of 45 Chinese patients with RA, 45 patients with osteoarthritis (OA) and 44 age- and sex-matched (with the RA group) healthy control (HC) subjects were consecutively recruited for the present case-controlled study. In addition, the demographic and clinicopathological characteristics of the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…46 14-3-3η predicts disease activity of RA and its duration, and when combined with other biomarkers such as anti-CCP and RF, its diagnostic ability improves. [25][26][27] This has also been consistent with previous studies. 47 14-3-3η is a predictor of bone remodelling and RA related osteoporosis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…46 14-3-3η predicts disease activity of RA and its duration, and when combined with other biomarkers such as anti-CCP and RF, its diagnostic ability improves. [25][26][27] This has also been consistent with previous studies. 47 14-3-3η is a predictor of bone remodelling and RA related osteoporosis.…”
Section: Discussionsupporting
confidence: 93%
“…The level of 14-3-3η was highest in the osteoporosis group compared to the normal group (p<0.05). 25 Similarly, another study showed that 14-3-3η positively correlated with inflammation and disease risk as reported by Tu J et al 26 14-3-3η was significantly increased in RA patients, and ROC analysis indicated that it served as a potential predictive marker for RA risk. 26 14-3-3η distinguished patients with established RA (disease duration >2 years) compared to early RA patients ([?…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…In Japanese patients with established RA, patients with positive 14-3-3η had a significantly higher DAS28 score, ESR level and CRP level than patients with negative 14-3-3η [9]. Tu et al [24] found that RA patients had a significantly higher serum 14-3-3η protein level than in osteoarthritic patients and control individuals.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, a previous study demonstrated that 14-3-3η may be involved in the pathogenesis of RA via promoting the formation of invadosomes through regulating the forkhead box O3/Snail axis ( 34 ). In another study, the serum levels of 14-3-3η were associated with an increased risk of RA and disease severity ( 35 ). Of note, emerging evidence has suggested that 14-3-3η serves a vital role in bone metabolism ( 13 , 19 ).…”
Section: Discussionmentioning
confidence: 99%